O čem govorimo, kadar govorimo o "našem" pravu - Božič, Katja (Pravni letopis, 2014)
Everyday discourse at very different levels is fairly uniform: that our legal system is chaotic, too complex, bureaucratic, impractical and unfair. Trust in the law, in legal certainty and in the rule of law should be immanent to the attitude towards that law that people experience as legitimate, i.e. the law which is, very simply put, acceptable and justified. Distrust in the law implies a severely undermined confidence in state institutions, that is, in the people who shape, adopt and enforce the law. The difference between the responses to the "law" and "our law" is expected and not at all surprising. If the law of the European Union is not perceived as "our" law, we thus indirectly do not count on all the rights and obligations resulting therefrom. And they are all but irrelevant. Through unawareness of this important fact, we are losing the opportunity to activate and mobilise in this field. More broadly, however, this denies or at least loosens the already poor identification with affiliation to the European Union. The story of trust in European Union law is probably similar to the story of trust in the national regulations; however, some other elements may be highlighted and exposed. The law is something relational, it exists in relationships between people and in relation to things. With the massive electoral abstinence, we are renouncing democracy; with the massive social apathy we are denying involvement in the social reality. If we want the situation to change, we should not remain silent. Each of us can probably contribute something towards restoring the respect of the law and trust into it.
Keywords: European Union; Evropska unija; identiteta; law; pravna država; pravna načela; pravo; Slovenia; Slovenija; zaupanje